The decline of natural law how American lawyers once used natural law and why they stopped - Banner, Stuart 1963- (Oxford University Press, 2021)
Before the late 19th century, natural law played an important role in the American legal system. Lawyers routinely used it in their arguments and judges often relied upon it in their opinions. Today, by contrast, natural law plays virtually no role in the legal system. When natural law was part of a lawyer's toolkit, lawyers thought of judges as finders of the law, but when natural law dropped out of the legal system, lawyers began thinking of judges as makers of the law instead. The Decline of Natural Law explores the causes and consequences of this change. It discusses the ways in which lawyers used natural law and why the concept seemed reasonable to them. It examines several long-term trends in legal thought that weakened the position of natural law, including the use of written constitutions, the gradual separation of the spheres of law and religion, the rapid growth of legal publishing, and the position of natural law in some of the 19th century's most contested legal issues. It describes the profession's rejection of natural law in the late 19th and early 20th centuries. And it explores the ways in which the legal system responded to the absence of natural law"--